2018
DOI: 10.1002/bmc.4322
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced HPLC‐MS/MS method for the quantitative determination of the co‐administered drugs ceftriaxone sodium and lidocaine hydrochloride in human plasma following an intramuscular injection and application to a pharmacokinetic study

Abstract: A sensitive HPLC-MS/MS method was established for the quantification of ceftriaxone sodium (CFT) and lidocaine HCl (LDC) in human plasma utilizing cefixime (CFX) and tadalafil (TDA) as internal standards. The analytes were extracted from human plasma by protein precipitation using acetonitrile. Chromatographic separation was performed on Kinetex C (50.0 × 4.6 mm, 5 μm particle size) column with methanol-0.01 M ammonium acetate pH 6.4 (70: 30, v/v) as mobile phase. Multiple reaction monitoring involving the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the literature research, no study was found regarding the simultaneous determination of TIN and LID in pharmaceutical preparations. It was determined that HPLC [14,15] and HPLC/MS/MS [16,17] methods were generally used in studies conducted separately for both active ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature research, no study was found regarding the simultaneous determination of TIN and LID in pharmaceutical preparations. It was determined that HPLC [14,15] and HPLC/MS/MS [16,17] methods were generally used in studies conducted separately for both active ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Literature shows a higher proportion of the usage of HPLC in the analysis of ceftriaxone in the aqueous and biological samples [ 14 ]. The methods studied for the analysis of ceftriaxone include high-performance liquid chromatography coupled with mass spectrometry detection (HPLC-MS) [ 14 , 71 , 72 ], high-performance liquid chromatography with detection by ultraviolet (HPLC-UV) [ 14 , 73 , 74 , 75 , 76 ], and high-performance liquid chromatography coupled with sequential mass spectrometry (HPLC-MS/MS) [ 14 , 77 , 78 , 79 , 80 , 81 ]. The referred methods studied for the analysis of ceftriaxone also include ultra-performance liquid chromatography with detection by ultraviolet (UPLC-UV) [ 14 , 82 ] and ultra-performance liquid chromatography coupled with sequential mass spectrometry (UPLC-MS/MS) [ 49 , 83 , 84 ].…”
Section: Methods Used To Analyze Antibioticsmentioning
confidence: 99%
“…The objective of this study was to develop and validate an accurate and sensitive bioanalytical method for ceftriaxone determination in low volume human plasma using LC-MS/MS. Only a few research publications have reported using LC-MS/MS for ceftriaxone determination in human biological samples [13][14][15][16] . Thus, this will be one of the first methods for ceftriaxone determination by LC-MS/MS and an alternative option to the already published methods.…”
Section: Introductionmentioning
confidence: 99%